2019
DOI: 10.1002/psc.3212
|View full text |Cite
|
Sign up to set email alerts
|

The effect of end‐group substitution on surface self‐assembly of peptides

Abstract: Biofouling, the undesirable accumulation of organisms onto surfaces, affects many areas including health, water, and energy. We previously designed a tripeptide that self‐assembles into a coating that prevents biofouling. The peptide comprises three amino acids: DOPA, which allows its adhesion to the surface, and two fluorinated phenylalanine residues that direct its self‐assembly into a coating and acquire it with antifouling properties. This short peptide has an ester group at its C‐terminus. To examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Such a difference in the assembly behaviour of the amino acid mimetic with a mere modification in the N-terminal residue is quite exciting and has been previously observed in the case of other peptides and amino acids, where the self-assembly behaviour was decisively altered by varying the end groups. 51,52 Furthermore, it was observed that the particles exhibited concentration dependent assembly behaviour and NBs were obtained at higher amino acid concentrations. Interestingly, we also observed that the formation of NBs can be tuned by varying microfluidics flow parameters.…”
Section: Papermentioning
confidence: 99%
“…Such a difference in the assembly behaviour of the amino acid mimetic with a mere modification in the N-terminal residue is quite exciting and has been previously observed in the case of other peptides and amino acids, where the self-assembly behaviour was decisively altered by varying the end groups. 51,52 Furthermore, it was observed that the particles exhibited concentration dependent assembly behaviour and NBs were obtained at higher amino acid concentrations. Interestingly, we also observed that the formation of NBs can be tuned by varying microfluidics flow parameters.…”
Section: Papermentioning
confidence: 99%
“…To address both of these criteria, fluoropeptide scaffolds comprised of dihydroxyphenylalanine (DOPA) residues have been designed to promote tissue adhesion of the antibacterial biomaterial. [27,139] Dolid et al demonstrated how antifouling activity of DOPA-based fluoropeptide coatings depend on C-terminal modifications. [27] Here, amide modifications were found to change the C F to promote host cell attachment and spreading (>35% viable cell coverage).…”
Section: Tissue Engineering and Implantsmentioning
confidence: 99%
“…[27,139] Dolid et al demonstrated how antifouling activity of DOPA-based fluoropeptide coatings depend on C-terminal modifications. [27] Here, amide modifications were found to change the C F to promote host cell attachment and spreading (>35% viable cell coverage). [139] Antibacterial resin dental composites have been Streptococcus mutans to 95%, while retaining similar biocompatibility and mechanical strength as commercial dental resins (Figure 9).…”
Section: Tissue Engineering and Implantsmentioning
confidence: 99%
See 2 more Smart Citations